Leguminosas de verão como cobertura do solo para produção de milho em sistema de plantio direto - Cieslik, Laurês Francisco (2014)
In southern Brazil the dominant agricultural model is the no-tillage system (SPD), with the predominant use of cool season grasses, especially oats. This species while being a great producer of biomass, has less potential for providing nitrogen for the following crop through recycling. Thus, the use of cover crops as summer legumes can fix nitrogen (N) in the absence of additional atmospheric nitrogen can be an effective strategy for local production system, because they occupy the ground and having idle period biomass production well above the grasses of winter. The present study aims to assess the effects of summer legumes grown in no-tillage in the off-season period with or without nitrogen complementation the agronomic parameters and yield of corn. The work was conducted in the years 2012 and 2013 in the experimental field of UTFPR Campus Dois Vizinhos in experimental design of randomized blocks in a factorial with three replications. In the main plots of 5 m x 10 m systems plant ground cover (factor A) and the split plots of 5 m x 5 m were established, factor B has been reported regarding the use of chemical nitrogen fertilizer. The main experiment consisted of seven systems plant summer cover Crotalária juncea (Crotalária juncea L.), Crotalária spectabilis (Crotalária spectabilis), Feijão de porco (Ensiformes canavalia), Guandu anão (Cajanus cajans L.), Lab lab (Dolichos lablab), Mucuna anã (Mucuna deeringiana), Mucuna preta (Mucuna aterrima) and maintained a system without the cover crop (fallow), associating these complementation of mineral N for corn (use of 180 kg ha-1 N as urea and absence). Reviews the development, production, decomposition and N by dry matter (MS) cover crops were conducted. In corn, the agronomic characteristics, the levels of N in biomass and leaf flag, and also grain yield were evaluated. In the 2012/2013 harvest mucuna preta and feijão de porco promoted a higher rate of ground cover at 30 DAS (57 and 56 % respectively). In both years the feijão de porco had the highest MS production and higher accumulation of N in MS. The higher rate of waste decomposition occurred with the use of feijão de porco and lab lab. The lowest rate of decomposition was observed in crotalária juncea and guandu anão. The use of legumes did not affect the stem diameter and plant height of maize. The feijão de porco, crotalária juncea and mucuna preta in the 2012/2013 harvest and lab lab in the 2013/2014 harvest , without the use of mineral N resulted in higher grain yield of corn the average of treatments with the addition of 180 kg ha-1 N.